1979
DOI: 10.1172/jci109532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spontaneous and experimentally induced canine prostatic hyperplasia.

Abstract: A B S T R A C T Spontaneous prostatic hyperplasia in the beagle appears to progress with age from a glandular to a cystic histological appearance. Prostatic hyperplasia can be induced in young beagles with intact testes by treatment for 4 mo with either dihydrotestosterone or 5a-androstane-3a,17,8-diol, alone, or with either of these steroids in combination with 17,3-estradiol.In contrast, the induction of prostatic hyperplasia in young castrated beagles, in which the gland had been allowed to involute for 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
139
1
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(154 citation statements)
references
References 19 publications
9
139
1
5
Order By: Relevance
“…61 In contrast to that in man, the enlarged prostate in the dog rarely results in urethral obstruction. 62 Broderick et al 63 developed a canine model of BPH that will secondarily result in partial urethral obstruction and impaired urodynamics.…”
Section: Bph Inductionmentioning
confidence: 96%
See 3 more Smart Citations
“…61 In contrast to that in man, the enlarged prostate in the dog rarely results in urethral obstruction. 62 Broderick et al 63 developed a canine model of BPH that will secondarily result in partial urethral obstruction and impaired urodynamics.…”
Section: Bph Inductionmentioning
confidence: 96%
“…19 In these animals, BPH is also an age-related disease. The onset of BPH in the dog may occur at as early as 2 ± 3 y of age, 61 but it occurs with high frequency in aged dogs. 64,65 Microscopic BPH was observed in all dogs after 6 y of age.…”
Section: Spontaneous Bphmentioning
confidence: 99%
See 2 more Smart Citations
“…3α-Diol is a weak androgen K d of 10 −6 M for the AR that is incapable of transactivation. Studies in rats (Orlowski, et al, 1983), dogs (DeKlerk, et al, 1979;Jacobi, ,et al 1978), marsupials (Shaw, et al, 2000) and humans (Horst, et al, 1975) have demonstrated that 3α-diol can be converted back to 5α-DHT to stimulate growth of the prostate, but the identity of the oxidative 3α-HSD responsible for this back reaction has remained elusive. Our data shows that "RoDH like 3α-HSD" (a short-chain dehydrogenase /reductase (SDR)) (Biswas and Russell, 1997) is responsible for this reaction in human prostate.…”
Section: Introductionmentioning
confidence: 99%